The Customer Satisfaction Analysis of SobaTani IPB - Ajriya, Ahmil; matoati, RIndang (Jurnal Agroekoteknologi Terapan, 2025)
The retail industry plays a pivotal role in Indonesia’s economic development, and it is estimated that the number of retail businesses in Indonesia in 2022 will exceed 90.000 resulting in intensifying competition, including in the freshmart retail sector. SobaTani is one of the freshmart businesses with a distinctive concept, but which continues to encounter challenges in terms of fluctuating income and transactions, particularly in the context of intense competition within the freshmart sector. An evaluation of SobaTani’s performance is required in order to ascertain and enhance customer satisfaction. This study aims to analyze the level of customer satisfaction at SobaTani IPB. The study utilized both primary and secondary data, which were subjected to an importance-performance analysis (IPA) and a customer satisfaction index (CSI) evaluation. The results demonstrated that 96% of the indicators were in accordance with the established standards. The identified areas for improvement, classified within quadrant I, included the accessibility of the location, the alignment of promotional content with the actual situation, and the presentation of products in a manner that minimizes consumer wait times. SobaTani’s customer satisfaction index (CSI) was found to be 86.38%, indicating a high level of satisfaction among SobaTani consumers.